2009
DOI: 10.1021/jp903293y
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Rate Coefficients for the Reactions of Atomic Bromine with Toluene, Tetrahydrofuran, and Tetrahydropyran

Abstract: The rate coefficients for the reactions of atomic bromine with toluene, tetrahydrofuran, and tetrahydropyran were measured from approximately 295 to 362 K using the relative rate method. Iso-octane was used as the reference compound for the reaction with toluene, and iso-octane and toluene were used as the reference compounds for the reaction with tetrahydrofuran; tetrahydrofuran was used as the reference compound for the reaction with tetrahydropyran. The rate coefficients were found to be unaffected by chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(74 citation statements)
references
References 17 publications
8
66
0
Order By: Relevance
“…Again, we note that these adjustments of the barrier heights are within the chemical accuracy of the ab initio methods used here. The adjusted barrier height of 10.4 kJ/mol agrees closely with the enthalpy of activation (ΔH=10.8normalkJ/normalmol) reported by Giri and Roscoe 15 who calculated the thermodynamic parameters from their experimental kinetic data. The calculated values of the equilibrium constant ( K 1a ), rate coefficients ( k 1b ), and overall rate coefficients [ k 1, ov ( T ) = K 1 a ( T ) × k 1 b ( T )] are provided in Table 3.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Again, we note that these adjustments of the barrier heights are within the chemical accuracy of the ab initio methods used here. The adjusted barrier height of 10.4 kJ/mol agrees closely with the enthalpy of activation (ΔH=10.8normalkJ/normalmol) reported by Giri and Roscoe 15 who calculated the thermodynamic parameters from their experimental kinetic data. The calculated values of the equilibrium constant ( K 1a ), rate coefficients ( k 1b ), and overall rate coefficients [ k 1, ov ( T ) = K 1 a ( T ) × k 1 b ( T )] are provided in Table 3.…”
Section: Resultssupporting
confidence: 86%
“…There was evidence in the literature 22 that the reaction of benzene with Br was unmeasurably slow, suggesting that the abstraction of a ring hydrogen was unimportant. In our earlier experimental work, 15 we found that the reaction of Br with toluene occurred with a conveniently measurable rate coefficient. This suggested that the bromine atom reacted primarily with the methyl hydrogens.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The low-temperature reactions of cyclic ethers, such as THF, tetrahydropyran (THP) and 1,4-dioxane, with halogen atoms (Br and Cl) have recently been investigated using experimental and computational methods [26][27][28] . The reactions of these cyclic ethers with Cl showed similar reactivity ( k ≈ 10 14 cm 3 mol −1 s −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 6-311G standard basis set used in electronic structure calculations for bromine possesses a contraction error of 25.6 kcal/mol À1 for Br( 2 P), which is appreciably higher than the contraction errors of the other five p-block elements of the fourth period. Using the relative rate method, the temperature dependence of the rate coefficients for the reactions of atomic Br 2 with toluene, tetrahydrofuran, and tetrahydropyran were measured over the range of 295 to 362 K. 28 Based on their results the authors suggest that differences in the entropy of activation may be just as important as the enthalpy of activation to explain variations in reactivity. 26 The AM1* semiempirical molecular orbital technique now includes parameters for bromine and iodine.…”
mentioning
confidence: 99%